Beauty contests and irrational exuberance: A neoclassical approach - George-Marios Angeletos; Guido Lorenzoni; Alessandro Pavan (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2010)
The arrival of new, unfamiliar, investment opportunities is often associated with exuberant movements in asset prices and real economic activity. During these episodes of high uncertainty, financial markets look at the real sector for signals about the profitability of the new investment opportunities, and vice versa. In this paper, we study how such information spillovers impact the incentives that agents face when making their real economic decisions. On the positive front, we find that the sensitivity of equilibrium outcomes to noise and to higher-order uncertainty is amplified, exacerbating the disconnect from fundamentals. On the normative front, we find that these effects are symptoms of constrained inefficiency; we then identify policies that can improve welfare without requiring the government to have any informational advantage vis-a-vis the market. At the heart of these results is a distortion that induces a conventional neoclassical economy to behave as a Keynesian beauty contest and to exhibit fluctuations that may look like irrational exuberance to an outside observer.
Keywords: 330; mispricing; heterogeneous information; information-driven complementarities; volatility; inefficiency; beauty contests